Relations publiques et gouvernance participative : une vision partagée du « vivre ensemble »? - Stéphanie Yates (Communiquer)
Since they generally have a questionable reputation, public relations are rarely associated with the notion of participatory governance. Nonetheless, the theoretical developments elaborated over the last twenty-five years are in phase with this emerging field, notably with James E. Grunig’s dialogical approach to public relations and Robert L. Heath’s fully functioning society theory. In this perspective, public relations play a conciliatory function that, through dialogue, allows for a better understanding of the positions held by different actors in democratic societies, to a genuine inter-influence between organizations and stakeholders, and ultimately to more harmonious relations. This contribution is thus an attempt to reconcile two worlds that we persist to conceive apart from each other. We conclude by acknowledging that the gap between theoretical models and the actual practice of public relations in contemporary contexts contributes to reduce these activities to the traditional diffusion model. In that sense, the paradigm shift that would put public relations at the core of participatory governance is still in waiting.